2018
DOI: 10.18376/jesp/2018/v14/i1/111289
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the Percentage Body Fat on Muscular Endurance of Junior Free Style Wrestlers

Abstract: The aim of this study was to observe effect of the percentage body fat on muscular endurance of junior free style wrestlers according to their weight categories. Method: one hundred fifty (N=150) male junior free style wrestlers were participated as subjects and they were further divided into five groups according to their weight categories, each group was comprised of thirty wrestlers. Body fat percentage was estimated by using Durnin and Womersley equation, In Push up test, recorded the number of push-ups pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
0
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 13 publications
2
0
0
Order By: Relevance
“…According to the findings, there was a weak negative correlation between body fat percentage and flexibility that was statistically nonsignificant, possibly due to the study's small sample size. This finding is consistent with Singh P et al [23] study, which found a negative relationship between body fat percentage and flexibility in adults. As a result, more research with a large sample size is required to confirm the relationship between body fat percentage and hamstring flexibility.…”
Section: Resultssupporting
confidence: 93%
“…According to the findings, there was a weak negative correlation between body fat percentage and flexibility that was statistically nonsignificant, possibly due to the study's small sample size. This finding is consistent with Singh P et al [23] study, which found a negative relationship between body fat percentage and flexibility in adults. As a result, more research with a large sample size is required to confirm the relationship between body fat percentage and hamstring flexibility.…”
Section: Resultssupporting
confidence: 93%
“…According to the findings, there was a weak negative correlation between body fat percentage and flexibility that was statistically nonsignificant, possibly due to the study's small sample size. This finding is consistent with Singh P et al's [23] study, which found a negative relationship between body fat percentage and flexibility in adults. As a result, more research with a large sample size is required to confirm the relationship between body fat percentage and hamstring flexibility.…”
Section: Resultssupporting
confidence: 92%